The Impact of Foreign Aid on Foreign Direct Investment in Emerging Markets - Kunofiwa Tsaurai (Comparative Economic Research, 2025)
This study explores the influence of foreign aid on foreign direct investment (FDI) in emerging markets using panel data analysis methods (fixed effects, fully modified ordinary least squares (FMOLS), and ordinary least squares (OLS)) with data from 2004 to 2019. It also examines whether financial development is a channel through which FDI is influenced by foreign aid in emerging markets using the same econometric estimation methods. Fixed effects and FMOLS indicate that foreign aid significantly improves FDI. However, contrary to the available literature, FMOLS and pooled OLS indicate that financial development significantly reduces FDI. The interaction between foreign aid and financial development did not show a significant impact on FDI across all three panel methods. Pooled OLS analysis shows that human capital development significantly enhances FDI. Furthermore, all the panel methods indicate that employment and infrastructure development positively influence FDI. Emerging markets also need to implement employment, human capital, and infrastructure development-enhancing policies and strategies to attract more and significant FDI inflows. They also need to implement policies that encourage the inflow of foreign aid to boost FDI. Future research should focus on estimating the optimal level of foreign aid needed to attract significant FDI into emerging markets.